THE ROLE OF SUPERVISION CONSULTANTS IN TIME PERFORMANCE OF COASTAL PROTECTION CONSTRUCTION PROJECTS IN JAKARTA - Tidaryo Kusumo; Endah Kurniyaningrum (RADJA PUBLIKA, 2026)
Coastal protection construction projects in Jakarta have a high level of complexity due to the influence of hydrodynamic conditions, soft soil, logistical limitations, and social dynamics of coastal communities. These conditions require the role of an effective supervisory consultant to ensure the achievement of project time performance. This study aims to analyze the role of supervisory consultants on time performance in coastal protection construction projects in Jakarta and formulate priorities for delay mitigation actions. The research method uses a quantitative and qualitative descriptive approach with a case study on the Coastal Protection Construction Project in Jakarta Phase 4 Package 1. Primary data were obtained through field observations, interviews, and questionnaires with related parties, while secondary data came from contract documents, progress reports, and project implementation schedules. Data analysis was carried out using the Schedule Performance Variance (SPV) method to measure time performance and the Analytical Hierarchy Process (AHP) to determine the priority of mitigation actions. The results of the study indicate that project delays are influenced by technical, logistical, administrative, and socio-environmental factors. The supervisory consultant plays a significant role in time control through technical, managerial, and administrative supervision. The AHP results indicate that accelerating material delivery and improving piling methods on soft soil are the main priorities in improving project time performance. This study confirms that optimizing the role of supervisory consultants can increase the effectiveness of time control in coastal protection construction projects in coastal areas.